Antibacterial properties of chitosan isolated from the black soldier fly, Hermetia illucens - Teo, Hui Peng; Law, Ke Wei; Chan, Eric Wei Chiang; Soo, Michelle Oi Yoon (Penerbit Universiti Kebangsaan Malaysia, 2022)
Insects are receiving wide attention as alternative food and feed resources, and for the production of useful by-products such as chitin, which can be converted into chitosan, a natural antibacterial agent. The larvae of Hermetia illucens, commonly known as Black Soldier Fly (BSF), can be reared on organic waste substrates and can be produced on a large scale. In this study, we focused on the antibacterial activity of chitosan obtained from BSF. Chitin from different growth phases of BSF was isolated using chemical treatments, characterized, and further synthesized into chitosan by deacetylation. The identities and structures of all isolated and synthesized compounds were verified using Fourier-transform infrared spectroscopy (FTIR). The antibacterial effect of BSF chitosan compounds against pathogenic bacteria were assessed with the determination of a minimum inhibitory concentration (MIC). Results showed that the chitin content increased gradually during the transition from larvae to adult BSF, with the highest amount obtained in the pupal stage. In the antibacterial susceptibility assay, Staphylococcus aureus was the most resistant to the action of BSF chitosan, with no significant effect exerted on its growth. For other species of bacteria, BSF chitosan could only restrict bacterial growth at concentrations of 0.25% or 0.5%, with the two most susceptible species being identified as Pseudomonas aeruginosa and Serratia marcescens. In conclusion, BSF chitosan exhibited antibacterial activity against different bacteria with varying sensitivities, in which the chitosan concentration was demonstrated to play an essential role.